Family ethics : practices for Christians - Rubio, Julie Hanlon (Moral traditions series., 2010)
How can ordinary Christians find moral guidance for the mundane dilemmas they confront in their daily lives? To answer this question, Julie Hanlon Rubio brings together a rich Catholic theology of marriage and a strong commitment to social justice to focus on the place where the ethics of ordinary life are played out: the family. Sex, money, eating, spirituality, and service. According to Rubio, all are areas for practical application of an ethics of the family. In each area, intentional practices can function as acts of resistance to a cultural and middle-class conformity that promotes materi.